Analysis of Sea Surface Temperature Changes and Its Impact on the Coastal Ecosystem of Saugi Island, Pangkep Regency - Nur, Medar M.; Nasrul, Nasrul; Hasrin, Sri Wahyuni; Rasyid, Angriani; Bunga, Imanuel Allo; R, Rifaldi.; Kausarani, Rini; Nurviana, Siti; Maru, Rosmini (Jurnal Ilmu Alam dan Lingkungan, 2025)
Sea surface temperature (SST) is a key parameter in the study of marine ecosystems, which plays an important role in determining the biological and physical dynamics of waters. This study analyzes changes in sea surface temperature in Saugi Island and its impact on coastal ecosystems. Using spatial analysis methods through remote sensing using Aqua Modis satellite imagery, sea surface temperature data were collected from August to September 2024. The results show that sea surface temperatures vary between 30°C and 36°C, with an average reaching 31.3°C. This increase in temperature has the potential to affect the metabolism and reproduction of marine organisms, as well as worsen the condition of coastal ecosystems due to seawater acidification and salinity fluctuations. This study aims to provide insight into the dynamics of sea temperature changes and the need for mitigation measures to protect ecosystems and improve the sustainability of coastal communities. This study is expected to be the basis for developing strategies in dealing with changes in sea surface temperature that have an impact on coastal ecosystems with mitigation efforts of the temperature monitoring network and eco wave initiative.